Фіскальні аспекти митного контролю при застосуванні механізму "країна походження товарів" - Чорна, Тетяна Миколаївна; Гребельник, Олександр Петрович; Мельник, Олена Володимирівна; Сагайдак, Ірина Степанівна; Микитенко, Тетяна Владиславівна (Дніпровський державний аграрно-економічний університет, 2024)
Стаття присвячена аналізу фіскальних аспектів митного контролю країни походження товарів. Проаналізовано значення країни походження товарів для забезпечення інтересів держави. Показано, що для митних цілей існує розподіл на два типи походження товарів: непреференційне і преференційне. З’ясовано, що визначення країни походження товарів є одним з найважливіших завдань під час проведення митного контролю, оскільки від цього залежить розмір нарахованого мита. Проаналізовано дані щодо результатів діяльності органів ДМС України в частині контролю країни походження товарів та обсягів додаткових надходжень до державного бюджету. Показано, основні фіскальні ризики залежно від задекларованої країни походження товару. Сформульовано пропозиції щодо удосконалення контролю країни походження товарів, серед яких: розвиток системи електронної взаємодії та отримання відомостей про дозвільні документи безпосередньо від уповноважених виконавчих органів України; додаткове використання швидких і ефективних методів контролю характеристик товару з метою визначення країни походження; удосконалення механізму міжнародної взаємодії відомств; активне впровадження інформаційних технологій та підтримка відповідної кваліфікації посадових осіб митних органів та ін.

The article analyses the fiscal aspects of customs control of the country of origin of goods. The author analyses the importance of the country of origin of goods for ensuring the interests of the State, and in particular, reveals that the accuracy of the declaration of the country of origin of goods affects the level of taxation of goods transported across the customs border of Ukraine, application of non-tariff regulation of foreign economic activity, prohibitions and/or restrictions on movement, and also ensures that these goods are recorded in foreign trade statistics. In addition, the correct determination of the country of origin of goods is a key to preventing the entry of counterfeit and low-quality products into the territory of the State. The article shows that for customs purposes there is a division into two types of origin of goods: nonpreferential and preferential, each of which is confirmed by the relevant types of documents. At the same time, the procedure for documentary confirmation of the country of origin of goods is determined by the rules (protocols) of origin which are an integral part of free trade agreements and the Customs Code of Ukraine. It is found that determination of the country of origin of goods is one of the most important tasks in the course of customs control, since the amount of the accrued duty depends on this, and therefore the amount of budget revenues. The author analyses the data on the results of the activities of the State Customs Service of Ukraine in terms of controlling the country of origin of goods and the amount of additional revenues to the State budget. It is shown that the main fiscal risks, depending on the declared country of origin of goods, are: application of preferences under free trade agreements; taxation of goods subject to differentiated duty rates of the Customs Tariff of Ukraine; taxation of goods with special types of duty. The proposals aimed at improving the control of the country of origin of goods are formulated, including: development of the system of electronic interaction and obtaining information on permits directly from the authorised executive bodies of Ukraine, rather than from participants in foreign economic activity; additional use of fast and effective methods of controlling the characteristics of goods in order to determine the country of origin, as well as special technical means; improvement of the mechanism of international cooperation between agencies, active introduction of information technologies and support.
Keywords: країна походження товарів; митний контроль; тарифні преференції; митні платежі; митний тариф; country of origin; customs control; tariff preferences; customs payments; customs tariff